2012, No. 12, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Financial accounting theory and practiceGreta Vetriakaitė, Kristina Rudžionienė, Evaluation of USA GAAP and EU accounting harmonization, 7Jūratė Klusavičiūtė, Kristina Rudžionienė, Determinants of liabilities‘ disclosure in financial statements of Lithuanian listed companies, 19Renata Smirnova, Kristina Rudžionienė, Factors of the corporate social responsibility disclosure in financial statements, 31Rasa Subačienė, Džemilė Jakubauskaitė, Aspects of financial and tax accounting of tangible fixed assets, 41Financial analysis and measurement, Gerda Venckevičiūtė, Gražina Jatulevičienė, Economy,  efficiency,  effectiveness and efficacy (four Es‘) concept in performance measurement, 49Lukas Giriūnas, Internal control and its place in a company‘s management structure, 58Jovita Pliustienė, Strategic planning for tourism and rural tourism sector development opportunities, 67Neringa Slavinskaitė, Complex evaluation of operating activity efficiency of dairy industry companies, 82Jokūbas Leipus, Jonas Mackevičius, The stability of Islamic Banks throughout the global financial crisis, 95Liuda Villis, The essence and models of the supervision of major financial institutions, 105
Keywords: none